Benefits and Costs of For-Profit Public Education - Molnar, Alex (Education Policy Analysis Archives, 2001)
As a policy initiative, for-profit operation of public schools has not lived up to the claims of its proponents. An examination of issues such as teaching methods, academic achievement, autonomy, local control, and the image and influence of for-profit public schools suggests that "for-profits" are unlikely to succeed in the long term in improving the overall quality of public education. They do, however, seem capable of harming public schools.